METASTASIS OTAK TIPE MILIER PADA KASUS ADENOKARSINOMA PARU DENGAN MUTASI EGFR T790M - I Made Oka Adnyana; Ni Luh Putu Eka Arisanti (PERDOSNI, 2020)
Brain metastasis is the most common intracranial tumor with the number of events exceeding primary brain tumors. It still holds high mortality and morbidity rate to date. Most of the metastases are macroscopic parenchymal mass lesions with surrounding edema and occurred in the gray-white matter junction. Miliary brain metastasis is a rare condition with generally poor prognosis. A male patient, 51 years old, Balinese, was admitted with decreasing consciousness since 1 week ago. The patient was diagnosed with lung adenocarcinoma with positive EGFR mutation in March 2019 and since April 2019 was started taking gefitinib 200mg every 24 hours. The patient also had intermittent headaches accompanied by vomiting, the head MRI with contrast showed multiple-miliary punctate lesions on almost every brain tissue, suggesting miliary type metastases. Further investigation revealed a positive EGFR T790M mutation. Miliary type brain metastases is a rare condition with poor prognosis. Chemotherapy and radiotherapy do not provide a satisfactory result. Miliary metastases pattern should be considered in differential diagnoses of patients with progressive dementia and multiple lesions as numerous diseases have similar head CT scan appearances. To this date, there is no standard therapy regimen for miliary brain metastases but some studies showed that the combination of whole-brain radiotherapy and EGFR tyrosine kinase inhibitor was deemed as having beneficial effects. The survival rate on these cases range from 14 days to 24 months. Keywords: Adenocarcinoma, brain, lung, metastases, miliary type